2002
DOI: 10.2337/diabetes.51.3.803
|View full text |Cite
|
Sign up to set email alerts
|

Association of Fasting Plasma Glucose With Heart Rate Recovery in Healthy Adults

Abstract: Diabetes is associated with abnormal autonomic function and increased mortality. Abnormal heart rate recovery after exercise, a measure of autonomic dysfunction, is also associated with increased mortality. The objective of this study was to determine the association of fasting plasma glucose with abnormal heart rate recovery and its prognostic importance in healthy adults. We studied 5,190 healthy adults who did not have medically treated diabetes (mean age 45 years, 39% women), were enrolled in the Lipid Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
96
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(108 citation statements)
references
References 29 publications
10
96
0
2
Order By: Relevance
“…While some studies have demonstrated reduced measures of HRVor heart rate in persons with IFG compared with those with NFG [8][9][10], others showed no such differences [11][12][13][14][15]. Moreover, these studies did not evaluate the complete spectrum of glucose intolerance, i.e.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…While some studies have demonstrated reduced measures of HRVor heart rate in persons with IFG compared with those with NFG [8][9][10], others showed no such differences [11][12][13][14][15]. Moreover, these studies did not evaluate the complete spectrum of glucose intolerance, i.e.…”
Section: Discussionmentioning
confidence: 98%
“…Nine population-based studies assessing the relationship between HRV and glucose intolerance have been published [8][9][10][11][12][13][14][15][16]. While some studies have demonstrated reduced measures of HRVor heart rate in persons with IFG compared with those with NFG [8][9][10], others showed no such differences [11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Slower HRR following exercise has been linked to the metabolic syndrome and several of its components in young adults (6,7) and elderly people (8). Since the presence of metabolic syndrome conveys an increased risk of metabolic disease and operates early in children and adolescents (9,10), it is possible that the adverse effects of the metabolic components on HRR might function in young ages.…”
mentioning
confidence: 99%
“…It is a new index clinically significant in evaluating the cardiac autonomic system, especially the parasympathetic nervous function after exercise. Panzer et al reported that abnormal HRR was present among 42% of patients with impaired fasting glucose and 50% with diabetes 8 . HRR is considered as a strong predictor of increased cardiovascular disease and overall mortality, independently of other cardiac risk factors 9 .Several studies have also shown that abnormal HRR is a predictor of poor prognosis in patients with heart failure 10,11 .…”
Section: Introductionmentioning
confidence: 99%